Extended storage and glucose exhaustion are associated with apoptotic changes in platelets stored in additive solution. Issue 2 (4th October 2015) - Johnson, Lacey; Schubert, Peter; Tan, Shereen; Devine, Dana V.; Marks, Denese C.
Abstract : BACKGROUND: The storage of platelets (PLTs) in additive solution (AS) may facilitate improved PLT quality and possibly extension of the PLT shelf life. A minimum amount of plasma is required when PLTs are stored in AS, as a source of glucose. The aim of this study was to assess the effect of reducing the plasma carryover to 20% on PLT quality when stored in SSP+ for an extended period. STUDY DESIGN AND METHODS: Using a pool‐and‐split design, buffy coat–derived PLTs were stored in either 30% plasma/SSP+ or 20% plasma/SSP+. In vitro analyses were carried out to Day 10. Metabolites and markers of PLT activation and apoptosis were measured using a blood gas analyzer and flow cytometry. PLT apoptotic protein expression was investigated by Western blotting. RESULTS: Glucose exhaustion occurred in the 20% plasma group between Day 7 and Day 10. The surface expression of P‐selectin and PAC‐1 was comparable on Day 10 in both groups, suggesting that the PLTs were not activated. However, the exposure of phosphatidylserine and the number of phosphatidylserine‐positive microparticles were significantly higher in the 20% group on Day 10. The expression of the proapoptotic proteins Bak, Bax, and cleaved caspase‐3 were higher in the 20% plasma group by Day 7 of storage, compared to the 30% plasma group. CONCLUSION: Exhaustion of glucose was associated with a proapoptotic phenotype. Results such as these should be considered before extending the PLT shelf life beyond 7 days, particularly when stored in ASs lacking glucose with low plasma carryover.